Three new species of Hyalella (Crustacea: Amphipoda: Hyalellidae) from the Southern Brazilian Coastal Plain - Talhaferro, Jordan Tuparai; Bueno, Alessandra Angélica De Pádua; Pires, Mateus Marques; Stenert, Cristina; Maltchik, Leonardo; Kotzian, Carla Bender (Zootaxa, 2021)
In this study, three new species of Hyalella (Crustacea: Amphipoda: Hyalellidae) are described based on specimens collected in wetlands located in three freshwater ecoregions (Southeastern Mata Atlântica, Tramandaí-Mampituba and Laguna dos Patos) of the southern Brazilian Coastal Plain (states of Rio Grande do Sul and Santa Catarina). Hyalella minuana n. sp. was recorded in the southernmost region of the state of Rio Grande do Sul. This species is characterized by presenting smooth body surface, epimeral plates not acuminated, nine serrate setae on the inner face of gnathopod 1, and peduncle of uropod 3 with four cuspidate setae with accessory seta and without plumose seta on the margin of the telson. Hyalella lagoana n. sp. was recorded in the northern region of Rio Grande do Sul and southern region of Santa Catarina. This species shows body surface smooth, epimeral plates not acuminated, nine serrate setae on the inner face of gnathopod 1, peduncle of uropod 3 with five cuspidate setae with accessory seta, and telson with six cuspidate setae with accessory seta without plumose seta on the margins. Hyalella sambaqui n. sp. was recorded in the state of Santa Catarina. This species is characterized by presenting smooth body surface, epimeral plates not acuminated, six serrate setae on the inner face of gnathopod 1, peduncle of uropod 3 with three cuspidate setae with accessory seta, and telson with three cuspidate setae with accessory seta and four plumose setae on the margin of the telson. The new records elevates the known diversity of species of Hyalella in the Brazilian territory to 33 species (19 in the southern Brazilian region) and to 83 species in the Americas.